Characterization of the complete plastid genome of Lysimachia christinae Hance (Primulaceae) - Cai-Yun Zhang; Hai-Fei Yan; Feng-Ying Wang (Mitochondrial DNA. Part B. Resources, 2021)
Lysimachia christinae Hance is widely distributed in subtropical China at the elevational range from 500–2300 m. The species is an important medicinal herb for treating jaundice, urinary disorders, and the liver. Here, we sequenced and characterized the whole plastid genome of L. christinae. It is 154,810 bp in length, containing two copies of inverted repeat (IR) regions (26,034 bp, each), a large single-copy (LSC) region (84,809 bp), and a small single-copy (SSC) region (17,933 bp). It has 114 genes, of which 80 are protein-coding, 30 are tRNA, and 4 are rRNA genes. The ML tree indicates L. christinae is closely related to Lysimachia congestiflora Hemsl. This genome information can help us better construct a backbone phylogeny of Lysimachia in the future.